2021
DOI: 10.1177/09596836211033198
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative synthesis of Holocene vegetation change in Nigeria (Western Africa)

Abstract: Understanding long-term (centennial–millennial scale) ecosystem stability and dynamics are key to sustainable management and conservation of ecosystem processes under the currently changing climate. Fossil pollen records offer the possibility to investigate long-term changes in vegetation composition and diversity on regional and continental scales. Such studies have been conducted in temperate systems, but are underrepresented in the tropics, especially in Africa. This study attempts to synthesize pollen reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
2
1
0
Order By: Relevance
“…Our results contribute to the assumption that the origin of the LHRC is probably a combination of climate change and human impacts (Bayon et al 2019;Adeleye et al 2021). Both these conditions were met in Loundoungou where savannah termite mounds can still be observed but not in Mokabi where forest termite mounds are present.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our results contribute to the assumption that the origin of the LHRC is probably a combination of climate change and human impacts (Bayon et al 2019;Adeleye et al 2021). Both these conditions were met in Loundoungou where savannah termite mounds can still be observed but not in Mokabi where forest termite mounds are present.…”
Section: Discussionsupporting
confidence: 60%
“…However, recently some authors have shown flexibility in their statements and have put forward less clear-cut hypotheses. Adeleye et al (2021) and Bayon et al (2019) claim that paleoclimatic change was the main factor of the LHRC, but that anthropogenic impact cannot be excluded from the scenario since it is very difficult to quantify. In our study, evidence of past human occupation, such as shards of pottery, scorias, and charcoal, was found in Loundoungou (Freycon et al 2018), consistent with the presence of old savannah termite mounds.…”
Section: Discussionmentioning
confidence: 99%
“…Orbital parameters alone insufficiently explain such anomalies in the long sedimentary records. The spatial discontinuity of the termination event as captured by models (Hopcroft and Valdes, 2021) and the proxy records (Adeleye et al, 2021) support the notion that local disturbance ecologies, potentially associated with human technologies, could have accelerated the tempo and magnitude of some threshold crossing events during the terminal AHP in northern Africa.…”
Section: Neolithic Pastoral Ecologies Of Northern Africasupporting
confidence: 56%